New Competitions and Contracts: Sports Entrepreneurs and Litigation from a Historical Perspective. Issue 7 (24th May 2018) - Greenfield, Steve
Abstract: Entrepreneurial activities in professional sport often involve the disruption of the existing structures and relationships. A prime example is the revolution in sports broadcasting that has increased in commercial importance as the subscription-based model has developed. Governing bodies across several sports have faced challenges based on an entrepreneur identifying a new competition or even a new game format linked to a broadcasting opportunity. If these new ventures cannot or will not be accommodated a legal dispute may arise to determine what rights exist and which body can exercise them. Cricket and rugby union offer contrasting examples; in the former the dispute between the international authorities and World Series Cricket led to an acrimonious dispute and litigation in the High Court. Rugby union managed to successfully incorporate the move from amateurism to professionalism in collaboration with News Corporation despite the threat posed by the new rugby league competition. On an individual level, legal disputes have arisen as sporting talent has sought new commercial opportunities that requires release from existing contractual arrangements. This piece first considers the original relationship of sport and law articulated, by Edward Grayson. It then adapts the framework proposed by Stephen Hardy and analyses how the law has interacted with these elements and what principles, if any, can be identified in the relationship with sports entrepreneurship.